Evaluation and Strategy for Managing Ecological-Based Coral Reef Rehabilitation in Pramuka Island, Kepulauan Seribu - Shifa Fauziah; Fredinan Yulianda; Mennofatria Boer (Faculty of Fisheries and Marine Science, Brawijaya University, 2022)
Evaluation of rehabilitation is needed for planning a more sustainable rehabilitation program. This study aims to evaluate the implementation by formulating ecological parameters that affect the implementation of coral reef rehabilitation and determine the score and weight to determine the success rate and arrange strategi for managing coral reef rehabilitation. In this research used descriptive method, with the determination of key parameters and evaluation scores, based on literature study. Determination of the weight of the rehabilitation evaluation using PCA analysis. Retrieval of research data is done by direct survey on coral reef rehabilitation area on Pramuka Island. The rehabilitation success class clasified as of “very successful”, “successful”, “unsuccessful” and “very unsuccessful” classes. The results showed that there were 4 locations for coral reef rehabilitation ecologically with the category of unsuccessful and 1 location of coral reef rehabilitation with the category of very unsuccessful. The recommended rehabilitation strategy is to emphasize the government's commitment as the main force of management to improve the quality of the results of coral reef rehabilitation and increase the quality of coral reef and fishery monitoring activities. It was also a simultaneously maintaining of rehabilitated coral reefs, minimally every 6 months.